Two new Oedanomerus species from Zimbabwe (Coleoptera: Scarabaeidae: Melolonthinae: Tanyproctini) - Sehnal, Richard (Zootaxa, 2018)
Oedanomerus Waterhouse, 1875 (Coleoptera: Scarabaeidae: Melolonthinae: Tanyproctini) was established for a single species Oedanomerus hirsutus Waterhouse, 1875 from Botswana. Arrow (1936) later described O. longicornis from Zambia and Frey (1960) described O. pilosus from Mozambique. Evans (1987) revised the genus and described O. capriviensis and O. bicolor from Namibia. Finally, Lacroix (2005) described O. snizeki from Zimbabwe, O. squamosus from Botswana, and O. uhligi from Namibia.